Libya's Post-Qaddafi Transition The Nation-Building Challenge - Chivvis, Christopher S. (RAND Corporation, 2012)
A year after Qaddafi's death, the light-footprint approach adopted for Libya's postwar transition is facing its most serious test. Security, the political transition, and economic development all present challenges. But if Libya's transitional authorities and the international community handle this issue set adroitly, Libya could still emerge as a positive force for democratic stability in North Africa and a valuable partner against al-Qaeda.